Neuroticism and Frontal EEG Asymmetry Correlated With Dynamic Facial Emotional Processing in Adolescents - Moshirian Farahi, Seyedeh Maryam; Asghari Ebrahimabad, Mohammad Javad; Gorji, Ali; Bigdeli, Imanollah; Moshirian Farahi, Seyed Mohammad Mahdi (Frontiers in Psychology, 2019)
The aim of this research was to investigate the link between resting frontal EEG asymmetry, neuroticism and the valence of emotional face processing in adolescents. Fifty right-handed adolescents (50 % male; mean age = 14.20, SD = 1.97) were selected from schools in Mashhad. In order to investigate variables, we used BFQ-C, ADFES-BIV, and EEG. All data were analyzed using SPSS 22. The results showed that neuroticism correlates with the valences of fear, disgust, sadness, and surprise, but not with happiness, anger, and neutral faces. Furthermore, it was found that N was significantly positively correlated with mid-frontal asymmetry (F3–F4), and the lateral-frontal (F7-F8), whereas no correlation was found between N and frontal pole (Fp1-Fp2). We found significant negative correlations between the valence of fear, Fp1-Fp2, F3-F4, and F7-F8. The interaction findings revealed that neuroticism*mid-frontal asymmetry can significantly affect the valence of fear. Therefore, neuroticism and mid-frontal EEG asymmetry may serve as a risk indicator for psychopathology.